The Hard Labour of Speculation: Shaping a Reflection on Methods - Marina Vishmidt (MaHKUscript, 2019)
Over the past years of critically engaged participation in the sphere of activity that has until recently been neutrally known as ‘contemporary art’1 from the perspective of a theorist, writer and teacher, I have been developing a constellation of ideas which both speak about (as an observer) and ‘speak nearby’ (as a participant) the imbrication of art with political and economic forces in the disaster capitalism of our era from the standpoint of the production of subjectivity and labour. I’ve come to call this constellation 'speculation as a mode of production'. This research essay will provide an introduction to what is intended with this designation, and hopefully be able to frame some tangents of inquiry not yet pursued under this imprimatur but which are nonetheless relevant.